Analisis Pengaruh PDRB, Umur Harapan Hidup, Rata-rata Lama Sekolah, dan Pengeluaran Perkapita terhadap Indeks Pembangunan Manusia di Provinsi Lampung - Triono, Wira; Simorangkir, Agnes Monica; Putri, Maharani Renika (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Human development is a crucial foundation for a country's progress, with the Human Development Index (HDI) as its main benchmark. Lampung Province faces challenges in the form of HDI achievements below the national average and the existence of development inequality between regions. This study aims to analyze the effect of Gross Regional Domestic Product (GRDP), Life Expectancy (UHH), Average Years of Schooling (RLS), and Expenditure per Capita (PP) on HDI in Lampung Province. The method used is multiple linear regression analysis on secondary data from 15 districts/cities in Lampung during the period 2020-2024. The results of the analysis show that the regression model involving the four independent variables is significantly better than the simpler model. The F-test (simultaneous) and t-test (partial) prove that GRDP, RLS, UHH, and PP together and individually have a significant influence on HDI at the 5% significance level. The model also proved to be valid and robust after fulfilling all classical assumption tests, namely residual normality, homoscedasticity, non-autocorrelation, and non-multicollinearity, resulting in the Best Linear Unbiased Estimator (BLUE) model. With an Adjusted R-squared value of 0.9925, this model shows a very high ability to explain variations in HDI. Interpretation of the model shows that Average Years of Schooling (AOLS) has the largest positive influence on HDI improvement.